Diagnosis and management of gastroenteropancreatic neuroendocrine neoplasms by nuclear medicine: Update and future perspective - Ma, Xing; Ding, Ying; Li, Wenliang; Li, Qiang; Yang, Hui (Frontiers in Oncology, 2022)
Gastrointestinal (GI) cancers are the second most common cause of cancer related deaths in the World. Neuroendocrine neoplasms (NENs) is a rare tumor that originated from peptidergic neurons and neuroendocrine cells. NENs occurs in all parts of the body, especially in stomach, intestine, pancreas and lung. These rare tumors are challenging to diagnose at earlier stages because of their wide anatomical distribution and complex clinical features. Traditional imaging methods including magnetic resonance imaging (MRI) and computed tomography (CT) are mostly of useful for detection of larger primary tumors that are 1cm in size. A new medical imaging specialty called nuclear medicine uses radioactive substances for both diagnostic and therapeutic purposes. Nuclear medicine imaging relies on the tissue-specific uptake of radiolabeled tracers. Nuclear medicine techniques can easily identify the NENs tissues for their ability to absorb and concentrate amine, precursors, and peptides, whereas the traditional imaging methods are difficult to perform well. The somatostatin receptor (SSTR) is a targetable receptor frequently expressed in the gastroenteropancreatic neuroendocrine neoplasms (GEP-NENs), and is a promising target for tumor-targeted therapies and radiography. SSTR based somatostatin receptor imaging and peptide receptor radionuclide therapy (PRRT) has emerged as a new hot subject in the diagnosis and treatment of GEP-NENs due to the rapid development of somatostatin analogues (SSAs) and radionuclide. This review aims to provide an overview of the current status of nuclear medicine imaging modalities in the imaging of GEP-NENs, and puts them in perspective of clinical practice.